Construire la mémoire du processus d’élaboration des plans locaux d’urbanisme à travers des storymaps, un levier pour la prise en compte du paysage dans l’aménagement des territoires - Charlotte Porcq; Laurence Le Dû-Blayo (Projets de Paysage)
This article describes an attempt to memorise the arbitration processes conducted during the elaboration of an urban development plan for the city of Vitré via storymaps or narrative maps used to address landscape planning issues within the framework of urban planning regulations. The project develops a method for constructing these narratives ex-post, by using records of the speeches of actors in situ, making it possible to complete the storymaps with events during or prior to the planning process. The storymaps make it possible to place the urban development plan within a more long-term geo-historical perspective of landscape planning. They suggest that the urban development plans could play a role in the memorising of perceptions of space which influence public action in a given period.